STUDI REFLEKTIF ANXIETY: FAKTOR, DAMPAK, DAN CARA MENGATASI BERDASARKAN PENGALAMAN PRIBADI PADA MAHASISWA BIMBINGAN PENYULUHAN ISLAM - Nasichah; Na’ilah Inne Ramadhini; Riyana Khairunnisa Hidayat (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This study aims to explore the causes of anxiety, its impacts on students of Islamic Guidance and Counseling (BPI), and the coping strategies they apply based on personal experiences. BPI students often face various pressures from academic demands, social expectations, and personal challenges. These include tight schedules, heavy workloads, emotional struggles, and balancing multiple responsibilities, all of which can contribute to anxiety. This research used a qualitative method with a reflective study approach. Data were collected through in-depth interviews with seven active BPI students who are involved in both academic and non-academic activities. The results show that anxiety influences students emotionally, physically, and academically. Symptoms include sleep disturbances, reduced focus, irritability, and decreased motivation in academic performance. In response, students used several reflective coping strategies, such as journaling, time management, regular physical exercise, and spiritual practices including prayer and self-reflection. These methods helped them identify the roots of their anxiety and develop better self-understanding. The integration of reflective practices with Islamic spiritual values proved effective in strengthening mental resilience. This study highlights the importance of providing reflective and spiritually integrated counseling services tailored to the context of Islamic Guidance and Counseling (BPI) students, promoting long-term mental well-being and personal growth.